Режими та характеристики енергоблоку електростанції з додатковим робочим трансформатором власних потреб - Пастух, Олена Романівна (Національний університет "Львівська політехніка", 2020)
У дисертаційній роботі обгрунтовано доцільність впровадження нових схемних вирішень електричної частини енергоблоків (ЕБ) з додатковим робочим трансформатором власних потреб (ДРТВП). Особливістю цих схем є те, що ДРТВП працює в режимі заданого навантаженням ЕБ струму, що забезпечує підтримання бажаної напруги на шинах власних потреб (ВП) як в усталених експлуатаційних режимах, так і під час коротких замикань в прилеглій до ЕБ електричній мережі. Результати оцінки вартості нових схем і втрат потужності в них, а також аналізу усталених режимів і перехідних процесів за допомогою комп'ютерної техніки показали: схеми ЕБ з ДРТВП без пристроїв РПН за техніко-економічними показниками можуть бути альтернативою до традиційних схем; під час режимів завантаження генератора активною потужністю, близькою до номінальної, і зміни напруг генератора й енергосистеми в достатньо широких межах на шинах ВП забезпечується допустима напруга; за динамічною та результуючою стійкістю режимів та напругами на шинах ВП схема з ДРТВП має кращі властивості порівняно з традиційною; схемі ЕБ з ДРТВП притаманна природна симетрувальна властивість щодо напруги на шинах ВП під час зовнішніх несиметричних КЗ. This Dissertation justifies the feasibility of introducing new scheme, technical decisions for the electrical part of power stations units, in particular, new option of the power supply system implementation for the auxiliaries with an additional auxiliary working transformer. The conducteds comprehensive investigation and analysis of their modes and characteristics. The fundamental difference between such systems and the traditional ones is the application and circuitry of the inclusion of an additional auxiliary transformer, which works simultaneously with a working auxiliary transformer on the busbar of the first transformation stage of the auxiliaries power supply system. At the same time, in accordance with the chosen values of the parameters of the system elements, in particular, coefficients of transformation of the two auxiliary working transformers, the mode of operation of the additional auxiliary working transformer will be close to the current source mode, the value of which will be determined by the current load of the generator power units, both in the stable operating modes and during external short circuits in the electric network adjacent to the power units. This is the additional auxiliary working transformer mode that provides the voltage level, sufficient for their electrical power. Approach of selecting nominal and total power of the working and additional auxiliary working transformer power units of electric power stations, which gives the opportunity to take into account both characteristic operating modes of the power units and the requirement to the desired voltage is offered. Develop the methodology of evaluation of active-power losses in the new electric power supply schemes of the power units with an additional auxiliary working transformer, which allows to take into account the operating features of their elements is offered. It is shown that the magnitude of active-power loss is practically equivalent in both new and traditional schemes. The conducted analysis and the calculation example for the power units with a 200 MW turbo-generator showed that the scheme with a working and additional auxiliary working electric power transformer with without on-load tap changing (OLTC) devices by technical and economic indicators can be an alternative to the traditional schemes with the auxiliary working transformer of own with the OLTC device. A generalized equivalent circuit of replacement of two-winding transformer for calculation of the steady state modes is created in this work, which allows to take into account the features of magnetic systems without bringing the coordinates of the mode of windings to one voltage level. As also – account work transformers operates in the modes given by voltage and given by current. Developed correspondingly mathematical model. It is shown that the resonant properties of the equivalent circuit of additional auxiliary working transformer of the power units of power plants, predetermined by the way of bonding of such transformer, require high accuracy calculation of values of parameters of branches. This needs to be considered during usage of software complexes for computer simulation of the steady state modes. Computer simulation allowed revealing peculiarities of the mathematical and digital models of additional auxiliary working transformer and recommendations for their implementation. It’s shown that for the power units with an additional auxiliary working transformer in modes of generator loading with nominal active power with the voltage change of the generator and electric power system in sufficiently wide limits voltage is provided on the buses of auxiliary, sufficient for their electrical power. It’s well-proven that dynamic and resultant stability of the modes and voltage on buses of an additional auxiliary working transformer scheme has better properties than the traditional scheme. It’s shown that during external symmetric and asymmetric short circuit the phase voltage on buses of the auxiliari are enough for the normal operation of the auxiliari receivers during the lifespan of the short circuit, the phase voltage unbalance is low and the residual voltage is higher and the currents of the elements of the electrical part are lower compared to the traditional circuit. This increases the efficiency of the the power units. In this paper, it’s established that the schemas of the has a natural symmetric property regarding the voltage on the buses of the auxiliari during external asymetric short circuits. Experiments on a static physical model of a fragment of an electrical part of a power unit with an additional working auxiliary transformer have proved that the natural properties of the investigated circuit provide its operation in a mode close to the current source mode, the value of which is determined by the current load of the power units. At the same time, natural properties power units with an additional auxiliary working transformer, unlike the traditional power unit without an additional working auxiliary transformer, provide the level of residual voltage on the auxiliary power unit basbars, sufficient for the operation of their electrical receivers in three-phase short-circuit modes. Comparative analysis and the evaluation of the mathematical and physical modelling results of the power unit with and without an additional auxiliary working transformer have confirmed the research effectiveness using appropriate mathematical and digital models of such schemes and software systems that provide the required accuracy of the results. The results of the dissertation work are implemented as a separate module under the name of VAT in the digital computing complex DAKAR. On the basis of theoretical studies and calculations, recommendations were given regarding the admissible areas of voltage change of the generator in the characteristic steady state modes. В диссертационной работе обосновано целесообразность внедрения новых схемных решений электрической части энергоблоков (ЭБ) с дополнительным рабочим трансформатором собственных нужд (ДРТСН). Особенностью этих схем является то, что ДРТСН работает в режиме заданного нагрузкой ЭБ тока, что обеспечивает желаемое напряжение на шинах собственных нужд (СН) как в установившихся эксплуатационных режимах, так и при коротких замыканиях в примыкающей к ЭБ электрической сети. Результаты оценки стоимости новых схем и потерь мощности в них, а также анализ установившихся режимов и переходных процессов с помощью компютерной техники показали: схемы ЭБ с ДРТСН без устройств РПН по технико-экономи-ческим показателям могут быть альтернативой традиционным схемам; при режимах загрузки генератора активной мощностью, близкой к номинальной, и изменении напряжений генератора и энергосистемы в довольно широких границах на шинах СН обеспечивается допустимое напряжение; по динамической и результирующей устойчивости режимов и напряжениям на шинах СН схема с ДРТСН обладает лучними качествами по сравнению с традиционной; схема ЭБ с ДРТСН имеет естественное симметрирующее свойство касательно напряжений на шинах СН при внешних несимметрических КЗ.
The modes and characteristics of a power unit of a power-station with an auxiliary working transformer of own necessities
Режимы и характеристики энергоблока электростанции с дополнительным робочим трансформатором собственных нужд
Keywords: електрична станція; енергоблок; трансформатор власних потреб; моделювання; регулювання напруги; усталений режим; коротке замикання; стійкість; electric power station; power unit; system auxiliary transformer; simulation; voltage control; steady state; shortcut; stability; электрическая станция; энергоблок; трансформатор собственных нужд; моделирование; регулирование напряжения; установившийся режим; короткое замыкание; устойчивость; 621.3.077.4:621.311.2.072(043.3)